Weeding of Collections in Sci-Tech Libraries, 1st edition - Mount, Ellis (Routledge, 2020)
In this book, first published in 1986, experts from the various specialties describe the weeding process in corporate, academic, and university libraries. Factors affecting the weeding of materials - lack of space, a desire to place materials in a more suitable library, changing goals of the library - are explored. Discussions concerning the choices for the disposal of items are insightful and innovative.